Pengujian Anomali Size Effect Di Pasar Modal Indonesia - Luh Gede Sri Artini; Ni Putu Ayu Darmayanti; Gede Merta Sudiartha (Faculty of Economics and Business Udayana University, 2020)
The research on the size effect anomaly in the Indonesian Capital Market aims to find out the effect of company size on the performance of the stock portfolio. Descriptive statistical analysis method is used to explain the distribution of data and independent sample tests to compare the performance of stock portfolios of Sharpe index of large-size stock portfolios and small size stock portfolios formed from stocks that is consistently included in the Compass Index 100 during 2012-2017. The results of the study show that the Sharpe index of large-size stock portfolios is better than the small-size stock portfolio. The results of different tests show that the mean difference is not significant, so it can be concluded that the anomaly size effect does not occur in the Indonesian Capital Market, especially in stocks listed on the Kompas 100 Index